Effect Of Perception On Sharia Banks And Variety Seeking On Customer Switching Intention From Conventional Banks To Sharia Banks In Bekasi City - Estu Banyu Ramadhani; Adril Hakim; Rianti Pratiwi (Jurnal Ekonomi dan Perbankan Syariah, 2019)
As known, the competition between banks in Indonesia is increasingly tight. Making each bank in various ways such as developing products, improving services, procuring promos, etc., continues to be carried out to get potential customers for the continuity of their business. Only banks are able to attract new consumers and retain old consumers who may be able to grow and develop for long periods of time. Therefore, it becomes a challenge for sharia bank marketers in creating marketing strategies in accordance with Islamic law. In this case, one of the things that can be done by Islamic bank marketers is to approach the community by identifying whether or not there are customers of conventional banks who want to move to Islamic banks. This study aims to determine the effect of customer perceptions of Islamic banks and variety seeking on the customer intention to switch from conventional banks to Islamic banks. Data collection techniques in this study were conducted by distributing questionnaires to all Muslim society in Bekasi City. Sampling is done by judgmental sampling technique so that it gets 101 samples. The research method used is quantitative associative research and data is processed using Partial Least Square (PLS). The results of this study indicate that only variable perception society about the bank sharia who influential significant effect on the customer intention to switch from conventional banks to Islamic banks, while variety seeking does not have a significant effect on the customer intention to switch from conventional banks to Islamic banks.